Entrepreneurial tendencies of migrants working in the care sector in Poland - Jolanta Maj; Sabina Kubiciel-Lodzińska (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The main goal of the paper is to assess the degree of intent to become entrepreneurial, and whether this intent influences perceived barriers and hindrances self-employment. Research Design & Methods: For the purpose of the study, we employed the approach of grounded theory. The sample included 42 immigrants from the care sector chosen in accordance with snowball sampling and Respondent Driven Sampling. Findings: Most immigrants did not think about setting up a business or rejected the idea due to various reasons, including their current legal status or the lack of financial resources, sufficient language, and professional competencies. Some of the respondents admitted that they would like to start their own business in the future. Implications & Recommendations: The implications include the identification of barriers perceived by immigrants, which may be an indicator for decision-makers about areas which require improvement in order to facilitate migrant entrepreneurship. Contribution & Value Added: The article contributes to the research on migrant entrepreneurship by analysing entrepreneurial tendencies of migrants working in a specific yet important sector and by showing novel causalities between psychological, social, and environmental factors and the degree of intent to become self-employed.
Keywords: L26; O15; F22; 330; migrant entrepreneurship; migrant entrepreneur; migrant self-employment; care sector; entrepreneurship; migrant entrepreneurship; migrant entrepreneur; migrant self-employment; care sector; entrepreneurship